Crystallinity Modulation of Layered Carbon Nitride for Enhanced Photocatalytic Activities. Issue 35 (20th July 2016) - Wang, Jianhai; Shen, Yanfei; Li, Ying; Liu, Songqin; Zhang, Yuanjian
Abstract: As an emerging metal‐free semiconductor, covalently bonded carbon nitride (CN) has attracted much attention in photocatalysis. However, drawbacks such as a high recombination rate of excited electrons and holes hinder its potential applications. Tailoring the crystallinity of semiconductors is an important way to suppress unwanted charge recombination, but has rarely been applied to CN so far. Herein, a simple method to synthesize CN of high crystallinity by protonation of specific intermediate species during conventional polymerization is reported. Interestingly, the as‐obtained CN exhibited improved photocatalytic activities of up to seven times those of the conventional bulk CN. This approach, with only a slight change to the conventional method, provides a facile way to effectively regulate the crystallinity of bulk CN to improve its photocatalytic activities and sheds light on large‐scale industrial applications of CN with high efficiency for sustainable energy. Abstract : On the edge : Carbon nitride of high crystallinity and preferred orientation was successfully developed by a facile protonation of specific intermediates during conventional thermal condensation (see figure). Both the short and long lifetimes of charge carriers in the modified carbon nitride increased, which led to an increased possibility of capturing excited electrons and holes by reactive substrates in photocatalytic reactions.